ETIKA ISLAM JAWA DALAM TEMBANG â€œGUNDUL-GUNDUL PACULâ€ - Samidi Khalim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article describes the symbolic meaning of Gundul-gundul Paculsong. This is a song in Javanese language which is popular among Javanesechildren. This song, has a deep moral message, such as humility and zuhd.Since they are famous as humble people, they use satire to convey messageswhile they are playing with their friends.